Mid-infrared chalcogenide glass fibre lasers for operation beyond 4 μm wavelength - Xiao, Boyu (2025)
The 3–50 μm Mid-infrared (MIR) wavelengths have vast potential across many applications, including healthcare, environmental monitoring, industrial process control and security systems, due to their overlap with the “fingerprint region” of molecular absorption. However, fibre-based light sources in the MIR range are currently limited, particularly beyond 4 μm. Chalcogenide glass optical fibres are promising candidates for enabling lasing in the beyond 4 μm, thanks to their broad MIR transmission window and capacity for rare earth dopant solubility. This project focuses on the development of fibre lasers beyond 4 μm, using Ce3+ doped step-index chalcogenide glass fibre. The MIR Photonics Group at the University of Nottingham reported the first fibre laser operating beyond 4 μm in 2021 but the power output was not measured and also there were difficulties in repeating the result with many fibre samples indicating an issue with fibre geometry or quality.